2019
DOI: 10.18203/2319-2003.ijbcp20194778
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study on incidence of adverse drug reactions in a tertiary care teaching hospital: a pharmacovigilance study

Abstract: Background: An adverse drug reaction (ADRs) is determined as response to a drug that is noxious unintended excludes therapeutic failures, overdose, drug abuse, noncompliance, and medication errors. The main aim of the study is to detect, understand and report ADR’S.Methods: This study is prospective observational study conducted for 6 months in in-patient setting in a tertiary care hospital. Naranjo’s, WHO causality scale, Siegel scale, Schumock and Thornton scale are used to assess ADR. Graph Pad Prism and SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…According to the organ affected analysis, our studies concluded that the dermatology system was more affected by the ADRs compared to other systems, Skin rash was commonly seen in the dermatology system. Our findings were similar to the study conducted by Kalyani et al [5].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…According to the organ affected analysis, our studies concluded that the dermatology system was more affected by the ADRs compared to other systems, Skin rash was commonly seen in the dermatology system. Our findings were similar to the study conducted by Kalyani et al [5].…”
Section: Discussionsupporting
confidence: 93%
“…Here probable cases were more found as compared to the possible. These findings were the same as the study conducted by S. SreAkshayaKalyani et.al [5,[8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations